Air pollution and out-of-hospital cardiac arrest risk. (25th November 2020) - Moderato, L; Lazzeroni, D; Biagi, A; Spezzano, T; Matrone, B; Piepoli, M.F; Binno, S; Villani, G.Q; Aschieri, D
Abstract: Introduction: Out-of-hospital cardiac arrest (OHCA) is a leading cause of death worldwide; it accounts for up to 50% of all cardiovascular deaths.It is well established that ambient air pollution triggers fatal and non-fatal cardiovascular events. However, the impact of air pollution on OHCA is still controversial. The objective of this study was to investigate the impact of short-term exposure to outdoor air pollutants on the incidence of OHCA in the urban area of Piacenza, Italy, one of the most polluted area in Europe. Methods: From 01/01/2010 to 31/12/2017 day-by-day PM10 and PM2.5 levels, as well as climatic data, were extracted from Environmental Protection Agency (ARPA) local monitoring stations. OHCA were extracted from the prospective registry of Community-based automated external defibrillator Cardiac arrest "Progetto Vita". OHCA data were included: audio recordings, event information and ECG tracings. Logistic regression analysis was used to estimate the association between the risk of OHC, expressed as odds ratios (OR), associated with the PM10 and PM2.5 levels. Results: Mean PM10 levels were 33±29 μg/m 3 and the safety threshold (50 μg/m 3 ) recommended by both WHO and Italian legislation has been exceeded for 535 days (17.5%). Mean PM 5 levels were 33±29 μg/m 3 . During the follow-up period, 880 OHCA were recorded on 750 days; the remaining 2174 days without OHCA were used as control days. Mean age of OHCA patients was 76±15 years; male gender was prevalent (55% male vs 45% female; <0.001). Concentration of PM10 and PM 2.5 were significantly higher on days with the occurrence of OHCA (PM10 levels: 37.7±22 μg/m 3 vs 32.7±19 μg/m 3 ; p<0.001; PM 2.5 levels: 26±16 vs 22±15 p<0.001). Risk of OHCA was significantly increased with the progressive increase of PM10 (OR: 1.009, 95% CI 1.004–1.015; p<0.001) and PM2.5 levels (OR 1.012, 95% CI 1.007–1.017; p<0.001). Interestingly, the above mentioned results remain independent even when correct for external temperature or season (PM 2.5 levels: p=0.01 – PM 10 levels: p=0.002), Moreover, dividing PM10 values in quintiles, a 1.9 fold higher risk of cardiac arrest has been showed in the highest quintile (Highest quintile cut-off: <48μg/m 3 ) Conclusions: In large cohort of patients from a high pollution area, both PM10 and PM2.5 levels are associated with the risk of Out-of-hospital cardiac arrest. Funding Acknowledgement: Type of funding source: None